THYROID CANCER RISK ATTRIBUTABLE TO THORAX COMPUTED TOMOGRAPHY (CT) EXAMINATION - Iza Nurzawani Che Isa,; Lim Jia Hui,; Thilageswary A/P Veerasingam, (Journal of Islamic, Social, Economics and Development, 2021)
This study was carried out to determine the radiation dose to thyroid and effectivelifetime risk of radiation-induced thyroid cancer from thorax CT examination. The risk ofradiation-induced thyroid cancer due to thorax CT examination is very much present andshould not be ignored. A total of 2168 set data of CT dose parameters for thorax CTexaminations were obtained retrospectively and analysed using CT-Expo and WAZA-ARI to getthe absorbed dose to thyroid organ. The dose to thyroid organ ranged from 7.95 mGy to 14.18mGy for HRCT examinations and 14.40 mGy to 16.99 mGy for TAP examinations. The organdoses were found to vary within the two analytical software packages. The effective lifetimerisk was calculated by multiplying equivalent dose and lifetime attributable risk (LAR) basedon Biological Effects in Ionizing Radiation (BEIR) Report VII. The demographic factor and theeffective risk of thyroid cancer were analyzed. Generally, there were significant differences inthe estimated risk among between gender, age and ethnic groups. The estimated risk for femaleswas shown to have a higher mean rank compared to male. Older people tended to have lowercancer risk compared to other age groups. Malays appeared to have a higher risk, followedby Indian and then Chinese. The effective cancer risk of radiation-induced thyroid cancerthrough thorax CT examination may be low but it is, nevertheless, important. Optimizationprotocols should not be ignored in the role of reducing radiation thyroid cancer risk to patients.